2020
DOI: 10.1002/cctc.202000422
|View full text |Cite
|
Sign up to set email alerts
|

How to Engineer Organic Solvent Resistant Enzymes: Insights from Combined Molecular Dynamics and Directed Evolution Study

Abstract: Expanding synthetic capabilities to routinely employ enzymes in organic solvents (OSs) is a dream for protein engineers and synthetic chemists. Despite significant advances in the field of protein engineering, general and transferable design principles to improve the OS resistance of enzymes are poorly understood. Herein, we report a combined computational and directed evolution study of Bacillus subtlis lipase A (BSLA) in three OSs (i. e., 1,4‐dioxane, dimethyl sulfoxide, 2,2,2‐trifluoroethanol) to devise a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(108 citation statements)
references
References 130 publications
8
100
0
Order By: Relevance
“…Additionally, there were no differences in terms of solvation performance in the substrate binding site (see more details in Figures S13–S15 and Table S6 in the Supporting Information). All results confirmed that the hydration shell played a critical role in influencing enzyme activity and resistance in organic (co‐)solvent environments [11b, 15c] …”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Additionally, there were no differences in terms of solvation performance in the substrate binding site (see more details in Figures S13–S15 and Table S6 in the Supporting Information). All results confirmed that the hydration shell played a critical role in influencing enzyme activity and resistance in organic (co‐)solvent environments [11b, 15c] …”
Section: Resultssupporting
confidence: 58%
“…A similar definition to that of the hydration level is also used for the organic‐solvent layer. A 6.8 Å cutoff was employed for DOX, as in a previous study [11b] . Number of water (d) or OS (e) molecules around the substituted residue positions in water and DOX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, very few reports have been conducted looking at the effect of naturally occurring substitutions on OS resistance of enzymes, but Bacillus subtilits Lipase A (BSLA) is a rare exception [9b, 34, 35] . A site saturation library (BSLA‐SSM) was constructed in our previous study and screened for variants with improved resistance toward three water‐miscible OSs (1,4‐dioxane (DOX), DMSO, 2,2,2‐trifluoroethanol (TFE)) [9b, 34–36] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, very few reports have been conducted looking at the effect of naturally occurring substitutions on OS resistance of enzymes, but Bacillus subtilits Lipase A (BSLA) is a rare exception [9b, 34, 35] . A site saturation library (BSLA‐SSM) was constructed in our previous study and screened for variants with improved resistance toward three water‐miscible OSs (1,4‐dioxane (DOX), DMSO, 2,2,2‐trifluoroethanol (TFE)) [9b, 34–36] . This library covers the full natural diversity at each of 181 amino acid positions consisting in total of 3440 BSLA variants (19×181 + wild‐type(WT)=3440) and is therefore well‐suited to study a putative correlation between salt bridges and OS resistance, thus opening the way to guide salt bridge engineering for obtaining OS and thermal resistance.…”
Section: Introductionmentioning
confidence: 99%